Assessment of SLEDAI score changes in systemic lupus erythematosus patients under low-dose interleukin-2 therapy: A meta-analysis - Dwi Soelistyoningsih; Hani Susianti; Handono Kalim; Kusworini Handono; Jonny Karunia Fajar (Elsevier, 2024)
Background: Interleukin-2 is being investigated as a potential therapeutic option in systemic lupus erythematosus (SLE), but the current findings regarding its effectiveness remained inconclusive. Objectives: To assess the association between the administration of low-dose interleukin-2 and the SLE Disease Activity Index (SLEDAI) score among SLE patients. Methods: A meta-analysis was conducted by gathering articles from Scopus, Pubmed, and Embase databases (PROSPERO registration ID: 451971). Essential data from each study was extracted, and the impact of administering low-dose interleukin-2 on the SLEDAI score in SLE patients was assessed using the inverse variance method. Results: We conducted an analysis of 7 articles involving 194 patients. Our study revealed that the administration of low-dose interleukin-2 was associated with a decrease in the SLEDAI score, showing an average reduction of −4.3 points from baseline. Furthermore, when comparing SLE patients treated with standard of care plus low-dose interleukin-2 to those receiving standard of care alone, we observed a significantly greater improvement in the SLEDAI score, with an average difference of 2.91 points. Conclusion: Our results indicate the potential beneficial impact of low-dose interleukin-2 in reducing disease activity and enhancing outcomes in SLE management.